Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.7150/ntno.50633
|View full text |Cite
|
Sign up to set email alerts
|

Neural precursors cells expanded in a 3D micro-engineered niche present enhanced therapeutic efficacy in vivo

Abstract: Rationale: Stem Cells (SCs) show a great potential in therapeutics for restoring and regenerating native tissues. The clinical translation of SCs therapies is currently hindered by the inability to expand SCs in vitro in large therapeutic dosages, while maintaining their safety and potency. The use of biomaterials allows for the generation of active biophysical signals for directing SCs fate through 3D micro-scaffolds, such as the one named "Nichoid", fabricated with two-photon laser polymerization with a spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 78 publications
2
21
1
Order By: Relevance
“…Nonetheless, in our study the combination of BLM and ICG triggered a disease that was clearly different from the typical BLM-induced lung brosis with a single administration corresponding to half of the dose we routinely use [16.] ICG is known to have a very short half-life and to be rapidly eliminated by the liver [25] upon intravenous administration, which seems to be in contrast with our ndings, as we detected a remarkable uorescence signal in lungs up to 21 days (Fig. 1).…”
Section: Discussioncontrasting
confidence: 99%
“…Nonetheless, in our study the combination of BLM and ICG triggered a disease that was clearly different from the typical BLM-induced lung brosis with a single administration corresponding to half of the dose we routinely use [16.] ICG is known to have a very short half-life and to be rapidly eliminated by the liver [25] upon intravenous administration, which seems to be in contrast with our ndings, as we detected a remarkable uorescence signal in lungs up to 21 days (Fig. 1).…”
Section: Discussioncontrasting
confidence: 99%
“…Altered expression of a similar gene in human has been associated with a susceptibility to myocardial infarction, and is involved in pathways that may contribute to the pathophysiology of schizophrenia. As already demonstrated, NPCs' growth inside the Nichoid present altered expression of genes that regulate mechanotransduction and stem cells fate [30,32]. Moreover, as there is a specific alteration of the lncRNAs expression as result of cells' expansion inside the Nichoid, we investigated whether this could be due to mechanotransduction or stemness-TF regulation.…”
Section: Role Of Lncrnas: Focus On Sequence Conservation and Relevance Of Human Homologuesmentioning
confidence: 87%
“…Here, we focused on the potential of the scaffold called “Nichoid” [ 24 , 25 ], engineered in the form of a 3D micro-grid in order to mimic the 3D microscopic architecture of a stem cells niche. The Nichoid already demonstrated able to maintain the stemness capacity of primary rat mesenchymal stem cells (MSCs), human bone marrow-derived MSCs, mouse ES cells [ 26 , 27 , 28 , 29 ] and NPCs [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Nichoid remodels the cytoskeleton and conditions cells to maintain a more spherical shape of the nuclei during proliferation with respect to cells grown on flat substrates [28]. Furthermore, we demonstrated that this scaffold maintains MSCs multipotency in vitro [31][32][33]. The architecture of the Nichoids allows optical inspection being composed of micrometric pores (tens of microns in size) and has a thickness of only 30 µm [24].…”
Section: Non-invasive Label-free Microscopy Techniques For Stem Cell mentioning
confidence: 88%